Spectrophotometric and dynamical properties of the soviet/russian constellation of molniya satellites. Issue 3 (September 2020) - Buzzoni, Alberto; Guichard, José; Alessi, Elisa Maria; Altavilla, Giuseppe; Figer, Alain; Carbognani, Albino; Tommei, Giacomo
Abstract: We report on the extended observing campaign of the surviving Soviet/Russian spacecraft Molniya, carried out in the years 2014–17 at Mexican and Italian telescopes. Spectrophotometry and astrodynamical analysis have been carried out for all the 43 demised payloads still in uncontrolled HEO orbit at late 2017, in order to assess dynamical and reflectance properties of such a wide family of virtually identical orbiting objects, as well as their long-term orbit evolution, according to full historic Two-Line Elements (TLE) datasets in synergy with mathematical modeling to properly size up the prevailing effect of lunisolar perturbation and atmospheric drag.